Ghrelin ameliorates A549 cell apoptosis caused by paraquat via p38-MAPK regulated mitochondrial apoptotic pathway - Cui, Shuqing; Nian, Qing; Chen, Gang; Wang, Xingyong; Zhang, Jinying; Qiu, Jianqing; Zhang, Zhiqiang (Toxicology (Amsterdam), 2019)
[Display omitted] •Ghrelin alleviated paraquat-induced A549 cell apoptosis.•Ghrelin suppressed paraquat-caused ROS production and p38-MAPK activation.•Ghrelin inhibited ROS-dependent mitochondrial apoptosis. Paraquat has relatively strong detrimental effects on humans and animals and can cause acute lung injury with high mortality. Ghrelin is a brain-gut peptide which plays important roles in regulating various physiological processes. This study investigated whether ghrelin could inhibit paraquat-induced lung injuries and attempted to elucidate the possible molecular mechanisms. A549 cells were preincubated with different concentrations of ghrelin and then treated with 200 μM of PQ for 24 h. Then cell survival, apoptosis, cellular oxidative stress and lipid peroxidation of A549 cells were detected after different treatments. Subsequently, we analyzed the mitochondrial membrane potential (ΔΨm) and measured caspase-3 activation in A549 cells. In addition, we investigated the activation of the MAPKs pathway and the function of p38-MAPK within mitochondrial apoptosis. Our study indicated that ghrelin administration improved cell viability and reduced apoptosis of PQ-treated A549 cells dose-dependently. Ghrelin treatment reduced the elevation of ROS and MDA, while improved GSH content in A549 cells after paraquat exposure. Moreover, we found that ghrelin dose-dependently increased ΔΨm and decreased caspase-3 activity. The phosphorylated p38 MAPK and JNK levels elevated following PQ exposure, while the phosphorylation of p38 MAPK decreased following ghrelin pretreatment. p38 MAPK siRNA or SB203580 pretreatment ameliorated PQ-caused cell injury and apoptosis related signals, however, the intracellular ROS production was not affected. N-Acetylcysteine (NAC), a classic antioxidant pretreatment decreased the phosphorylated p38 MAPK level and intracellular ROS production, alleviated cell injury, and inhibited apoptosis. The results showed that p38-MAPK pathway plays an important role in PQ-caused alveolar epithelial cell insult, and ghrelin might attenuate PQ-induced cell injury by inhibiting ROS-induced p38-MAPK modulated mitochondrial apoptotic pathway.